MENINGKATKAN PRESTASI HASIL BELAJAR PESERTA DIDIK MELALUI STRATEGI PEMBELAJARN KOOPERATIF JIGSAW PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Prayogo, Reza Adi; Albab H.S, Mohammad Iqbal Ulil (Lentera: Jurnal Ilmiah Kependidikan, 2021)
Education is a key role in that the development of a country, the quality of a country can be seen from the quality of an education It is in the country, as the 1945 bill commissioned it to be Enlightened national life. In shining the lives of nations is passed Through an arrangement of good national education. The educational arrangement Good ones can be good at learning. Success of the learning process Is shown with the high level of learning accomplished by learners. But At this time there are many learners whose learning is less Islamic religious education subjects. This proves there's nothing wrong and there is That has not been properly accomplished in the learning of teaching. One is The underlying cause of the low learning result is the lack of strategy Or calculated methods so that learning has not been working properly. Then The authors in this study are trying to explore the role of coopathic strategy